The concept and its meaning in modern science (Eurasian Journal of Philology Science and Education, 2018)
The article describes the «concept» of the term in modern science.The article describes the term of «concept» in modern science.The purpose of the article – to present an overview of scientific papers on the notion of concept, and to express attitudeto him.This term is considered from various perspectives:general scientific, linguistic, lingvocognitive, lingvocultural, given basic definitions of the concept.Authors as a working definition for the dissertation research choose interpretation of the term «concept» by V.A. Maslova:»Concepts – mental entities that have a name in the language and reflect the cultural and national representation of the human world.»The paper provides information about the structure and meaning of the concept presented in the scientific works of scholars such as Y.U. Stepanov, N.F. Alefirenko, V.I. Karasik, Sh.K. Zharkynbekova etc.